Balancing Consultation and Control: The Governance Role of Incubators in Entrepreneurial Development - Rohana Rinjani Manurung, Ully; Ruslaini (LPPM STIE Kasih Bangsa, 2024)
This qualitative literature review explores the governance role of incubators in entrepreneurial development, focusing on the balance between consultation and control. Incubators provide strategic guidance, resources, and networks, fostering innovation and strategic planning. Simultaneously, they exercise control by setting performance targets, tracking progress, and enforcing organizational structures, ensuring discipline and focus among entrepreneurs. The review highlights the complementary nature of these dual roles, which are essential for enabling start-ups to leverage both strategic guidance and operational discipline, contributing to their long-term success and sustainability. However, the study acknowledges limitations, including the need for empirical research and the exploration of additional governance dimensions. Further investigation is required to address these gaps and enhance our understanding of effective incubator governance.